2012
DOI: 10.1021/nl2039106
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Ferroelectric and Piezoelectric Properties of Sb2S3 Nanowire Arrays

Abstract: We report the first observation of piezoelectricity and ferroelectricity in individual Sb(2)S(3) nanowires embedded in anodic alumina templates. Switching spectroscopy-piezoresponse force microscopy (SS-PFM) measurements demonstrate that individual, c-axis-oriented Sb(2)S(3) nanowires exhibit ferroelectric as well as piezoelectric switching behavior. Sb(2)S(3) nanowires with nominal diameters of 200 and 100 nm showed d(33(eff)) values around 2 pm V(-1), while the piezo coefficient obtained for 50 nm diameter n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…Piezoresponse force microscopy (PFM) 68,73,82,83,84 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 26 frequency vertical PFM images, which given the low piezoresponses, topography cross-talk is likely also to be contributing to the images obtained. Since the films are comprised of some a-axis oriented grains as well as c-axis oriented grains ( Fig.…”
Section: (2) Ferroelectric Characterizationmentioning
confidence: 99%
“…Piezoresponse force microscopy (PFM) 68,73,82,83,84 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 26 frequency vertical PFM images, which given the low piezoresponses, topography cross-talk is likely also to be contributing to the images obtained. Since the films are comprised of some a-axis oriented grains as well as c-axis oriented grains ( Fig.…”
Section: (2) Ferroelectric Characterizationmentioning
confidence: 99%
“…However, it was found that Sb 2 S 3 nanowires have ferroelectric and piezoelectric switching behavior. 39 Furthermore, diminishing dimensions in ferroelectric/piezoelectric material such as Sb 2 S 3 reveal pronounced size dependent effects. 40 Therefore, these properties for bulk Sb 2 S 3 do not appear.…”
Section: The Ac Conductivity Analysismentioning
confidence: 99%
“…As a result, various Sb 2 S 3 materials with low dimentional [7,8] and flower-like [9,10] morphologies were prepared and extensively investigated for different purposes. Because of the outstanding absorption coefficient (a = 10 5 cm À1 ) in visible light region and relatively narrow band gap (about 1.7 eV), the applications of Sb 2 S 3 in sensitizer of photovoltaic cells [11,12] and photocatalysts [13][14][15] are of special interests.…”
Section: Introductionmentioning
confidence: 99%